Urban Heterophony and the Mediation of Place - McMurray, Peter (Lidé města, 2012)
This paper explores a variety of methodologies that offer ethnographic access to the kinds of "humanly organized sound" that typify urban acoustic spaces. The case studies draw from ongoing research on Sufi Muslim rituals in the Western Balkans (especially Kosovo), exploring ways in which sound articulates difference in cities (urban heterophony) and in so doing mediates notions of place. Three methodologies are put forward here: first, documentary sound studies, an attempt to bring together the kinds of media-rich practices of visual anthropology, acknowledging that academic prose has inherent limits in its ability to represent; second, media archaeology, a critical reappraisal of media archives (whether intentionally designated as archives or not) as repositories for audio and other materials-both physical and virtual-which simultaneously reflect and shape the priorities of the archive and its discursive practices; and, finally, aural flânerie, emphasizing passage through city spaces as a way of interrogating the boundaries and marginal spaces comprising the city. These ethnographic approaches offer a set of tools particularly suited to the socially enmeshed, collaborative realm of urban ethnomusicology, all the more so as technological developments raise questions about many of the basic premises of what constitutes fieldwork and ethnography in the past.